Factors associated with the high susceptibility to depression of women during the perimenopause. Issue 1 (8th December 2022) - Han, Hongying; Xia, Xiaowei; Zheng, Huirong; Zhong, Zhiyong; Zhao, Chongbang; Wang, Xianglan; Zhi, Ximei
Abstract: Objective: This study investigated the factors associated with the high susceptibility of perimenopausal women to depression. Methods: A total of 66 perimenopausal women participated in this study. The Zung self‐rating depression scale (SDS) was used to evaluate the intensity of depressive symptoms. The modified Kupperman index (KI) was used to assess common perimenopausal symptoms. Psychosocial factors were assessed via the Eysenck Personality Questionnaire, attitudes toward menopause checklist, and metacognition questionnaire (MCQ). Levels of serum estradiol, testosterone, and progesterone were determined. Results: There were statistically significant associations between SDS standard score and the KI scale score ( β  = .361, p  = .001), years of education ( β  = −.309, p  = .005), and F3 cognitive self‐consciousness score of MCQ ( β  = −.234, p  = .032; adjusted R 2  = .264, F  = 8.759, p  < .001). Conclusions: High susceptibility to depression of perimenopausal women may be related to lower educational level, more severe perimenopausal symptoms, and altered metacognition. Abstract : The perimenopause is a window of susceptibility to depression for women. The causes of the high susceptibility of perimenopausal women to depression remain unclear. High susceptibility to depression of perimenopausal women may be related to lower educational level, greater extraversion and unstable personality characteristics, more severe perimenopausal symptoms, and altered metacognition.